Applications of a conceptual framework to assess climate controls of forest tree diseases. Issue 6 (15th October 2021) - Hennon, Paul E.; Frankel, Susan J.; Woods, Alex J.; Worrall, James J.; Ramsfield, Tod D.; Zambino, Paul J.; Shaw, Dave C.; Ritóková, Gabriela; Warwell, Marcus V.; Norlander, Daniel; Mulvey, Robin L.; Shaw, Charles G.
Abstract: A conceptual framework for climate involvement in forest tree diseases was applied to seven examples to demonstrate its suitability for different disease types: cases where climate favours pathogen biology which then leads to tree mortality or where diseases are caused primarily by climate‐driven physiological injury or stress to trees. Hypotheses for climate involvement are derived from detection and monitoring data to express associations of weather or climate factors with disease development at several spatial and temporal scales. Research findings contribute to an understanding of temperature, precipitation and related climate variables that influence biotic and abiotic diseases. To demonstrate use of the framework, we accessed information from the literature which exposed data and information gaps. Among various simulated approaches to test associations of climate and disease, we found disease risk factor models that use climate inputs derived from monitoring and research provide the best understanding of climate–disease relationships. These model outputs project future disease scenarios that can be used to inform climate adaptation strategies. Conservation and management implications for current and likely future climatic conditions are provided for each disease example. The most common guidance in managed landscapes is to move the imperilled tree species to areas of lower projected climate risk and to favour non‐host, climate‐adapted tree species where the disease is occurring.